Social care and support needs of community-dwelling people with dementia and concurrent visual impairment. (2nd September 2017) - Nyman, Samuel Robert; Innes, Anthea; Heward, Michelle
ABSTRACT: Objectives: This study explored the social care and support needs of people with dementia and visual impairment, and the barriers and facilitators for meeting these needs. Method: Twenty-six semi-structured interviews were conducted: 21 joint and 5 individual interviews with the person with dementia and visual impairment ( n =4) or their family/paid carer ( n =1). Interviews were analysed thematically. Results: Three themes are presented. (1) Social care needs : having dementia can reduce an individual's ability to cope with their visual impairment, and lead to increased dependency and reduced daily stimulation. (2) Barriers to using technology to meet social care needs : difficulties were reported with learning to use unfamiliar technology and the cost of visual impairment aids, and for some, the presence of dementia made visual impairment aids unusable and vice versa. (3) Familiarity as a facilitator for meeting social care needs : living at home or taking furnishings and ornaments into a new home facilitated independence, and continuity of paid carers/volunteers facilitated the caring relationship between the individual and staff/volunteer. Conclusion: Care workers will better serve older people if they are aware of the social care and support needs that arise from having both dementia and visual impairment.